Movement Lawyering During a Crisis: How the Legal System Exploits the Labor of Activists and Undermines Movements - Aranda Osorno, Jaqueline (2021)
There is increasing recognition that the ableist trope “Justice is Blind” is a decades-long gaslighting of the American public, a distraction from the reality that our entire judicial system has always had a strict adherence to white supremacy. In the United States, the highest court continues to erode civil rights protections that were hard fought by Black Americans, many whose lives were taken during the journey. The legislature has codified laws that simultaneously extract wealth from communities of color and criminalize poverty. And the legal profession is one of the least diverse of any professional industry. Impartiality of legal systems, theory, and praxis is an illusion that we cannot afford to buy-into within our work toward a society with equitable distribution of resources and equal access to wellness and joy. This article aims to highlight how the inequities embedded within the legal system are exacerbated during public crises, and used to exploit the work of Black, indigenous, and other activists of color. The article will shed light on the ways in which traditional litigation strategies, resource allocation, and long-established ethics standards have undermined the work toward liberating historically oppressed communities in the United States. We will provide examples within the movement to defend Black lives, the movement to free our children from cages, and within the hurried push to release people from institutions in the height of the COVID-19 threat. The article will also discuss specific strategies that movement lawyers have successfully employed to shift power away from white supremacist institutions and into the communities with whom we are fighting alongside. We conclude with a call for lawyers and legal workers to think critically about how they leverage power structures within the legal field to work in tandem with movements during a crisis